Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien